“I Mean Who Likes Pedophiles”; Psychological Assessments of Men Who Have Sexually Offended. The Assessees’ Experiences - Chawke, Gemma (International journal of offender therapy and comparative criminology, 2024)
Pre-sentence psychological assessments of men who have sexually offended can provide useful information regarding an individual’s pathway to offending, risk of recidivism, and treatment needs. The outcome of the assessment can be used in court and has implications for the assessee and society at large. This research sought to explore offenders’ opinions regarding the clinicians’ approach to the assessment, to identify facilitative aspects of the clinicians’ style and to understand how accuracy and honesty can be enhanced in these interactions. Six interviews were conducted with sex offenders on completion of a pre-sentence forensic assessment at a private practice. Applying Interpretative Phenomenological Analysis, the findings highlighted the relational nature of the assessments, the assessees’ feelings of powerlessness, and their perceptions that the interaction helped them personally. The findings and approach advocated for by the assessees are discussed in terms of the associated ethical considerations and practice implications.